Resident and family spirituality in New Zealand residential aged care: an exploration. Issue 2 (3rd April 2022) - Frey, Rosemary; Balmer, Deborah
ABSTRACT: Semi-structured interviews were conducted to explore the constituents of spirituality for six residential aged care residents and six bereaved family members. Transcripts were analysed thematically and mapped to Lartey's integrated dimensions of spirituality. Findings suggest that spirituality is best described through the lens of connection, whether with the transcendent (religious belief), in oneself (identity), with another (family support), with a group (religion), or with space (RAC descriptor). The findings of this study highlight the importance of creating a balance between biomedical and spiritual aspects of care in RAC especially for culturally diverse residents and families.